PERAN PENDIDIKAN AGAMA ISLAM DALAM KELUARGA TERHADAP AKHLAK ANAK DI DESA JUNGKARE - Fadhil Al Hamdani, Iqbal; Hafidz, Hafidz (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
A Family education has great importance because it aims to shape an individual's personality. The family is considered the first institution that teaches good religious and ethical values ​​and respects other people in everyday life. The level of goodness or badness of a child can be seen from the role of the family in educating his morals. This research uses a qualitative research method with a case study approach, with data collection through observation, interviews and documentation. The results of research in Jungkare village show that Islamic religious education in the family has three important things, namely forming children's worship activities, teaching children manners, and instilling an attitude of honesty in children. Education in the family is an important aspect to build a person's behavior. Usually the education in a family is condacted with the religious values and ethics, which consists of behavior, manners and use attitude used in everydays life. The aim of this writing is to discuss the role of religious education in the family and society. This method used library research with the descriptive and explorative approach. The conclusions are that the role of the Islamic education: (1) as the foundation of religious education in a family which used to form the children’ good attitude and behavior, (2) functions as tools to convince people to the almighty of God, (3) as a foundation to build the society character for the Indonesian people to improve the nation.